2022
DOI: 10.3389/fgene.2022.987867
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a genetic contribution to the ossification of spinal ligaments in Ossification of Posterior Longitudinal Ligament and Diffuse idiopathic skeletal hyperostosis: A narrative review

Abstract: Diffuse Idiopathic Skeletal Hyperostosis (DISH) and Ossification of the Posterior Longitudinal Ligament (OPLL) are common disorders characterized by the ossification of spinal ligaments. The cause for this ossification is currently unknown but a genetic contribution has been hypothesized. Over the last decade, many studies on the genetics of ectopic calcification disorders have been performed, mainly on OPLL. Most of these studies were based on linkage analysis and case control association studies. Animal mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 144 publications
0
2
0
Order By: Relevance
“…Recently, genetic polymorphisms have been associated with DISH. 28 29 As such, genetic factors may be a critical feature that differentiates those at risk of advanced pathological mineralisation which may be independent of biological sex. The relative role of these potential underlying factors in the onset, progression and overall prevalence of DISH warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, genetic polymorphisms have been associated with DISH. 28 29 As such, genetic factors may be a critical feature that differentiates those at risk of advanced pathological mineralisation which may be independent of biological sex. The relative role of these potential underlying factors in the onset, progression and overall prevalence of DISH warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathologically, the following findings are characteristic of the disease: focal and diffuse ossification of the anterior longitudinal ligament and paraspinal connective tissue, ossification of the anulus fibrosus with degeneration of its peripheral fibers, hypervascularity, chronic infiltration with inflammato-ry cells, and periosteal ossification on the anterior surface of the vertebral bodies [6]. Recent studies regarding the complex etiopathogenesis of DISH have focused on the presence of a genetic predisposition, but a direct pathogenetic link between a particular genotype variant and the disease has not been demonstrated [7]. In a study by Parreira evidence of familial predisposition to the disease was found, pointing out to the presence of a genetic predispo-…”
Section: Discussionmentioning
confidence: 99%
“…Associations between DISH and dyslipidaemia or hyperuricaemia are also reported [52,62]. In comparison, HLA-B27 plays no role in the pathogenesis of DISH [63].…”
Section: Similarities and Differences In Ethiopathogenesismentioning
confidence: 92%